Impact of Teachers’ Empathy towards Adult Learners’ Struggles in Acquiring EFL - Nadia Zamal Chowdhury; Faheem Hasan Shahed (Har Press Indonesia, 2021)
This paper focuses on the role of empathy, one of the vital traits teachers are expected to possess, in the language acquisition process of Bangladeshi adult learners of English as a foreign language (EFL). It tries to assess if the presence of empathy in teachers’ approach has any significant impact on the pace of EFL acquisition of learners. This also investigates if the effect of empathy and associated emotions—such as sympathy and patience towards the struggle of learners—add positive and substantial speed to the learners’ progress. The study also tries to find out if the absence of a significant amount of empathy or complete absence of empathy slows down the acquisition process. A qualitative research conducted by applying multiple methodologies established the idea that the presence of empathy in teachers positively affects the performance of learners. The results also show that empathy in teachers may not always be very apparent while observing classes, but can be measured by considering the presence of other aspects that are crucial for effective teaching.